Radiotherapy in the Barwon South Western Region: A rural perspective. Issue 5 (5th August 2014) - Henry, Margaret J; Jones, Phil; Morrissy, Kate; Matheson, Leigh M; Pitson, Graham; Healy, Pat; Coory, Michael; Lynch, Rod; Chapman, Adam; Ashley, David
Abstract Introduction Cancer‐related mortality rates are higher in rural areas compared with urban regions. Whether there are corresponding geographical variations in radiotherapy utilisation rates (RURs) is the subject of this study. Methods RURs for the regional centre of Geelong and rural areas of the Barwon South Western Region were calculated using a population‐based database (2009). Results Lower RURs were observed for rural patients compared with the Geelong region for prostate cancer (15.7% vs 25.8%, P = 0.02), rectal cancer (32.8% vs 44.7%, P = 0.11), lymphoma (9.4% vs 26.2%, P = 0.05), and all cancers overall (25.6% vs 28.9%, P = 0.06). This lower rate was significant in men (rural, 19.9%; Geelong, 28.3%; P = 0.00) but not in women (rural, 33.6%; Geelong, 29.7%; P = 0.88). Time from diagnosis to radiotherapy was not significantly different for patients from the two regions. Tumour staging within the rural and Geelong regions was not significantly different for the major tumour streams of rectal, prostate and lung cancer (P = 0.61, P = 0.79, P = 0.43, respectively). A higher proportion of tumours were unstaged or unstageable in the rural region for lung (44% vs 18%, P < 0.01) and prostate (73% vs 57%, P < 0.01) cancer. Conclusion Lower RURs were observed in our rural region. Differences found within tumour streams and in men suggest a complexity of relationships that will require further study.